Antioxidant Activities of Photoinduced Phycogenic Silver Nanoparticles and Their Potential Applications - Vijayakumar Maduraimuthu; Jayappriyan Kothilmozhian Ranishree; Raja Mohan Gopalakrishnan; Brabakaran Ayyadurai; Rathinam Raja; Klaus Heese (MDPI AG, 2023)
While various methods exist for synthesizing silver nanoparticles (AgNPs), green synthesis has emerged as a promising approach due to its affordability, sustainability, and suitability for biomedical purposes. However, green synthesis is time-consuming, necessitating the development of efficient and cost-effective techniques to minimize reaction time. Consequently, researchers have turned their attention to photo-driven processes. In this study, we present the photoinduced bioreduction of silver nitrate (AgNO3) to AgNPs using an aqueous extract of Ulva lactuca, an edible green seaweed. The phytochemicals found in the seaweed functioned as both reducing and capping agents, while light served as a catalyst for biosynthesis. We explored the effects of different light intensities and wavelengths, the initial pH of the reaction mixture, and the exposure time on the biosynthesis of AgNPs. Confirmation of AgNP formation was achieved through the observation of a surface plasmon resonance band at 428 nm using an ultraviolet-visible (UV-vis) spectrophotometer. Fourier transform infrared spectroscopy (FTIR) revealed the presence of algae-derived phytochemicals bound to the outer surface of the synthesized AgNPs. Additionally, high-resolution transmission electron microscopy (HRTEM) and atomic force microscopy (AFM) images demonstrated that the NPs possessed a nearly spherical shape, ranging in size from 5 nm to 40 nm. The crystalline nature of the NPs was confirmed by selected area electron diffraction (SAED) and X-ray diffraction (XRD), with Bragg's diffraction pattern revealing peaks at 2θ = 38°, 44°, 64°, and 77°, corresponding to the planes of silver 111, 200, 220, and 311 in the face-centered cubic crystal lattice of metallic silver. Energy-dispersive X-ray spectroscopy (EDX) results exhibited a prominent peak at 3 keV, indicating an Ag elemental configuration. The highly negative zeta potential values provided further confirmation of the stability of AgNPs. Moreover, the reduction kinetics observed via UV-vis spectrophotometry demonstrated superior photocatalytic activity in the degradation of hazardous pollutant dyes, such as rhodamine B, methylene orange, Congo red, acridine orange, and Coomassie brilliant blue G-250. Consequently, our biosynthesized AgNPs hold great potential for various biomedical redox reaction applications.